Soil Systems - MDPI (MDPI, 2026)
Soil Systems - formerly Soils - is an international, scientific, peer-reviewed, open access journal on soil science, published monthly online by MDPI. The Italian Society of Soil Science (SISS) is affiliated with Soil Systems and its members receive discounts on the article processing charges.
Keywords: Suelos; Ciencias de la Tierra; Revistas depredadoras; Predatory journals